Análise da aplicação, no ensino técnico, de uma estratégia de ensino fundamentada na metodologia dos três momentos pedagógicos - Gontijo, Maria Eugênia (2014)
In this work, the objective was to analyze the contributions of questionable methodology, based on three pedagogical moments of Delizoicov to a group of professional technical course in Chemistry College CECON / Divinópolis, MG. For the three pedagogical moments were developed three classes and an activity that should be developed at home were necessary. At first it was presented to the students a problem that has been specially developed for the application of this work. The problem is linked to real situations of the city in which the college is located. In the second stage, students should develop an information booklet about what was proposed in the initial problem. In the third phase, students should respond at home to a list of problems which was also developed for the application of this work. In the analysis of the results was done using a categorization data as theoretical work of Bogdan and Biklen (1994). The results showed that students are not prepared to work with this methodology, which generates a little scared at the beginning of the process. But in short, the methodology presented here demonstrates the potential to contribute to the process of citizenship, humanization, and political development of student character and chemical knowledge through questioning. Keywords: Problematization, problematization methodology, chemical education